Haematologic malignancies associated with clozapine v. all other antipsychotic agents: a pharmacovigilance study in VigiBase® - Chrétien, Basile; Lelong‐Boulouard, Véronique; Chantepie, Sylvain; Sassier, Marion; Bertho, Mickael; Brazo, Perrine; Humbert, Xavier; Alexandre, Joachim; Fédrizzi, Sophie; Dolladille, Charles (Psychological Medicine, 2020)
BACKGROUND: Clozapine is mainly used in patients with treatment-resistant schizophrenia and may lead to potentially severe haematologic adverse events, such as agranulocytosis. Whether clozapine might be associated with haematologic malignancies is unknown. We aimed to assess the association between haematologic malignancies and clozapine using Vigibase®, the WHO pharmacovigilance database. METHODS: We performed a disproportionality analysis to compute reporting odds-ratio adjusted for age, sex and concurrent reporting of antineoplastic/immunomodulating agents (aROR) for clozapine and structurally related drugs (loxapine, olanzapine and quetiapine) compared with other antipsychotic drugs. Cases were malignant lymphoma and leukaemia reports. Non-cases were all other reports including at least one antipsychotic report. RESULTS: Of the 140 226 clozapine-associated reports, 493 were malignant lymphoma cases, and 275 were leukaemia cases. Clozapine was significantly associated with malignant lymphoma (aROR 9.14, 95% CI 7.75-10.77) and leukaemia (aROR 3.54, 95% CI 2.97-4.22). Patients suffering from those haematologic malignancies were significantly younger in the clozapine treatment group than patients treated with other medicines (p < 0.001). The median time to onset (available for 212 cases) was 5.1 years (IQR 2.2-9.9) for malignant lymphoma and 2.5 years (IQR 0.6-7.4) for leukaemia. The aROR by quartile of dose of clozapine in patients with haematologic malignancies suggested a dose-dependent association. CONCLUSIONS: Clozapine was significantly associated with a pharmacovigilance signal of haematologic malignancies. The risk-benefit balance of clozapine should be carefully assessed in patients with risk factors of haematologic malignancies. Clozapine should be used at the lowest effective posology.